2016
DOI: 10.1111/1751-7915.12380
|View full text |Cite
|
Sign up to set email alerts
|

High throughput genomic sequencing of bioaerosols in broiler chicken production facilities

Abstract: SummaryChronic inhalation exposure to agricultural dust promotes the development of chronic respiratory diseases among poultry workers. Poultry dust is composed of dander, chicken feed, litter bedding and microbes. However, the microbial composition and abundance has not been fully elucidated. Genomic DNA was extracted from settled dust and personal inhalable dust collected while performing litter sampling or mortality collection tasks. DNA libraries were sequenced using a paired‐end sequencing‐by‐synthesis ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
(59 reference statements)
2
21
0
Order By: Relevance
“…Bioaerosols measured could be composed of many types' of microorganisms ranging from bacteria, viruses, fungi, and other living components at varying concentrations. We expected that the majority of the bioaerosols would be of bacteria origin based on previous studies that have found bacterial species to be the most abundant in airborne agricultural dust (Karwowska, 2005;O'Brien et al, 2016;Oppliger et al, 2018 4.1.6.2 Press * to navigate to the flashing screen display of "---". Then press the "up" arrow 4.1.7 The pumps should start and the "black ball" on the rotameter should be floating at 4.0 L/Min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioaerosols measured could be composed of many types' of microorganisms ranging from bacteria, viruses, fungi, and other living components at varying concentrations. We expected that the majority of the bioaerosols would be of bacteria origin based on previous studies that have found bacterial species to be the most abundant in airborne agricultural dust (Karwowska, 2005;O'Brien et al, 2016;Oppliger et al, 2018 4.1.6.2 Press * to navigate to the flashing screen display of "---". Then press the "up" arrow 4.1.7 The pumps should start and the "black ball" on the rotameter should be floating at 4.0 L/Min.…”
Section: Resultsmentioning
confidence: 99%
“…Livestock workers are exposed to inorganic and organic dusts, gases, microorganisms, and biological constitutes. For example, poultry dust is composed of chicken feed, animal dander, urine, feces, and microbes (O'Brien et al, 2016).…”
Section: Components Of Livestock Bioaerosolsmentioning
confidence: 99%
“…Metagenomics sequencing is a novel technique that has been shown to quantify and characterize bioaerosols in various settings (King et al, 2016;Nonnenmann et al, 2010;O'Brien et al, 2016). However with time restraints for our study, culture based analysis was the quickest way to estimate concentrations of airborne organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular based analysis occurs when bioaerosols are collected or extracted into liquid solution where the DNA or RNA are analyzed, however viability of the microorganism may not be determined (ACGIH, 1999). Molecular analysis can include techniques such as polymerase chain reaction (PCR) or metagenomic techniques (e.g., shotgun sequencing) (King et al, 2016;Mukoda, Todd, & Sobsey, 1994;Nonnenmann, Bextine, Dowd, Gilmore, & Levin, 2010;O'Brien et al, 2016;Stetzenbach, Buttner, & Cruz, 2004). PCR is the oldest molecular method that quantifies microorganisms obtained in a sample and is limited for use in microorganisms which have a fully or partially sequenced genome (Mukoda et al, 1994).…”
Section: Analysis Methods For Collected Bioaerosolsmentioning
confidence: 99%
See 1 more Smart Citation